Evaluating institutional support systems for teacher well-being and work-life balance in Brunei Darussalam: Policies and practical outcomes - Afdanizan, Natashya; Mumin, Mas Ayu; Padilla-Valdez, Nena; Yueh, Lee Kok; Rahim, Atif (Edelweiss Applied Science and Technology, 2025)
This paper analyzes Brunei Darussalam’s education management support system designed for secondary school leaders and teachers to promote their well-being, including work-life balance. Brunei is a collectivist country that emphasizes Islamic beliefs, family, community, and religious commitments. Therefore, balancing work and family life involves managing professional responsibilities while fulfilling cultural and religious obligations. The influence of Brunei’s culture and religion on the support system framework warrants further examination. This study addresses this gap by exploring how these values are integrated into the education management support system for secondary school staff. Using qualitative methods, including in-depth interviews with education management personnel and a review of support programs, the research assesses the effectiveness of the current educational management framework and support initiatives. Findings suggest that teachers’ work-life balance is positively associated with supportive leadership practices and that school management significantly impacts teachers’ well-being. The study underscores the importance of Islamic principles and cultural norms in balancing professional and personal responsibilities. It also contributes to understanding how educational support management can develop sustainable support systems that enhance teachers’ professional experiences and promote healthier work-life balance within Brunei’s educational institutions.